Jan Rohde Go Go Show. (Poznań : [s.n.], 1966)
Afisz inf. o koncercie zespołu szwedzkiego 1.02.1966 r. w Hali Stoczni w Gdańsku.
Keywords: Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- życie artystyczne